Advances in macro-scale laser processing. Issue 2 (2018) - Schmidt, Michael; Zäh, Michael; Li, Lin; Duflou, Joost; Overmeyer, Ludger; Vollertsen, Frank
Abstract: Laser material processing is a technology with an increasing number of industrial applications, especially for aviation and automotive. The present keynote paper focusses on the advances in macro-scale laser processing, meaning that the laser generated structures are large enough to be visible with the naked eye. Next to that, also the reasons for the advances, especially the improvements regarding the power and the beam quality of the laser sources, the higher capabilities of the systems technologies and an increasing process understanding are shown. Nevertheless, challenges like a holistic understanding of the physical phenomena and the evolution of defects in some processing methods remain to be solved in future.